2016
DOI: 10.1016/j.psychres.2016.01.022
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of functional disabilities and perceived cognitive dysfunction in patients with major depressive disorder in South Korea: The PERFORM-K study

Abstract: PERFORM-K was a cross-sectional observational study that investigated functional disability, productivity and quality of life in MDD outpatients in South Korea, and the associations of these with depressive symptoms, perceived cognitive dysfunction and other factors. A total of 312 outpatients who started antidepressant monotherapy underwent a single study interview. Physicians and patients assessed depression severity. Patients also assessed: perceived cognitive dysfunction, functional disability, impaired pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 41 publications
21
38
1
Order By: Relevance
“…Cognitive dysfunction is highly prevalent in people with depression and has a significant impact on functioning (Jaeger et al, 2006;McIntyre et al, 2013;Shilyansky et al, 2016). In a recent, cross-sectional, observational study in South Korea, greater functional disability and impairment in daily activities, including worse work-related productivity outcomes, were associated with more severe perceived cognitive dysfunction (Kim et al, 2016). The domains of executive function, working memory, episodic memory, attention and psychomotor processing speed are commonly affected in people with depression (McIntyre et al, 2013;Shilyansky et al, 2016), with poorer performance in neuropsychological tests being in the order of small (0.2) to medium (0.5) effect sizes compared to healthy individuals (Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive dysfunction is highly prevalent in people with depression and has a significant impact on functioning (Jaeger et al, 2006;McIntyre et al, 2013;Shilyansky et al, 2016). In a recent, cross-sectional, observational study in South Korea, greater functional disability and impairment in daily activities, including worse work-related productivity outcomes, were associated with more severe perceived cognitive dysfunction (Kim et al, 2016). The domains of executive function, working memory, episodic memory, attention and psychomotor processing speed are commonly affected in people with depression (McIntyre et al, 2013;Shilyansky et al, 2016), with poorer performance in neuropsychological tests being in the order of small (0.2) to medium (0.5) effect sizes compared to healthy individuals (Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study cognitive impairment was significantly affected by the severity of depression, where the total score of cognitive impairment increased with severity of depression (P-value=0.001). A previous study (Miskowiak, et al 2012) suggested that severity of depression may be a predictor of cognitive impairment, while other previous studies (Fava, et al 2009;kim, et al 2016), reported a weak association between cognitive dysfunction and depression severity. In a study from Japan on participants aged 65 years and older, it was reported that cognitive impairment was more common in persons with depression (Hidaka, et al 2012).…”
Section: Discussion:-mentioning
confidence: 92%
“…Cognitive impairment in retrospective memory domain was the highest among the other domains, the mean scores for individuals regarding memory (retrospective and prospective) increased by increasing the severity of depression (P-value=0.001), however (Kim, et al 2016;Lam, et al 2013) revealed that planning/organization and concentration/attention domains were predominances than memory domain. Regarding planning of individuals, the impairment of planning was increased with the severity of depression (P-value=0.001).…”
Section: Discussion:-mentioning
confidence: 93%
See 1 more Smart Citation
“…There is evidence that cognitive dysfunction is related to poor social functioning in patients with depressive disorders (Kim et al 2016;Woo et al 2016). It has been reported that cognitive dysfunction is already present at an early stage of depressive disorders and is maintained even in remission (Woo et al 2016).…”
Section: Introductionmentioning
confidence: 99%